Enhancing herbage growth, yield and quality of stevia (stevia rebaudiana bertoni) using bio-organic nutrients in varied soil media - Calapardo, Mara Jean Marielle; Manigo, Bryl I. (Penerbit Universiti Kebangsaan Malaysia, 2024)
The present method of stevia propagation is still insufficient to meet its increasing demand. Moreover, the use of organic inputs as substitutes for inorganic fertilizers to improve soil quality and productivity is also desired. In this study, the effects of bio-organic nutrients and different growing media compositions on Stevia’s herbage growth, yield and quality were determined. A completely randomized design was used with 20 rooted stem cuttings per replication at one cutting per potting bag, laid in a 4 × 4 factorial arrangement. Growing Media (garden soil alone [GS]; GS + rice hull [RH]; GS + vermicompost [VC]; and GS+RH+VC) served as factor A while bio-organic nutrients (fermented fruit juice [FFJ]; vermi tea [VT]; seaweed tea [ST] and control) as factor B. There were 16 treatment combinations replicated four times. Results showed that GS+RH+VC consistently improved the survival rate, plant height, leaf and shoot count per plant, weight (fresh and dry), and herbage yield of Stevia. Furthermore, VT boosted the herbage yield and visual quality. In terms of interaction effects, plants grown in garden soil mixed with vermicompost (GS+VC) with VT application developed more leaves than other treatment combinations. Hence, these bio-nutrients and growing media composition significantly enhanced the production of Stevia.